Mesoscopic Numerical Simulation of Fracture Process and Failure Mechanism of Concrete Based on Convex Aggregate Model - Yijiang Peng; Xiyun Chen; Liping Ying; Ying Chen; Lijuan Zhang (Advances in Materials Science and Engineering)
To investigate the fracture process and failure mechanism of concrete subjected to uniaxial compressive loading, a new finite element method—the base force element method (BFEM)—was adopted in the modeling of numerical simulation. At mesoscale, concrete is considered as a three-phase heterogeneous material composed of aggregate particles, cement mortar, and the interfacial transition zones between the two phases. A two-dimensional random convex aggregate model was established using the principle of the area equivalence method. A multistage linear damage constitutive model that can describe nonlinear behavior of concrete under mechanical stress was proposed. The mechanical properties of concrete mesoscopic components are determined. The numerical simulation results indicate that the base force element method can be applied to predict the failure pattern of concrete under compressive loading, which have a good accordance with the available experiment data. The stress contour plots were given and used to analyze the failure mechanism of concrete. The effects of specimen size on the strength of concrete material were studied. It is found that compressive strength of concrete decreases as the specimen size increases. In addition, the influences of aggregate distribution, coarse aggregate content, and end friction on concrete performance are explored.